PS4:80 Hydroxychloroquine in lupus pregnancy: a meta-analysis of individual participant data. (21st March 2018) - Eudy, A; Petri, M; Fischer-Betz, R; Mokbel, A; Nalli, C; Andreoli, L; Tincani, A; Molad, Y; Gladman, D; Urowitz, M
Abstract : Purpose: Our current knowledge about how to treat lupus in pregnancy derives from small prospective or retrospective cohorts. The goal of this individual participant meta-analysis was to pool data from multiple prospective cohorts to answer the clinical question of whether hydroxychloroquine (HCQ) treatment affects pregnancy outcomes Methods: The literature was searched for prospective cohorts of pregnancies among women with lupus. HCQ use was defined as use any time during pregnancy. Outcomes of interest included fetal loss, preterm birth, high disease, and preeclampsia. Data from each cohort were collected and analysed individually. Pooled ORs were calculated by random-effect models in Review Manager. Due to multiple pregnancies per patient, one pregnancy was randomly selected per patient. Primary analysis included only women with first trimester visits (6 cohorts). Subgroup analyses were stratified by a history of nephritis, APS, and disease activity at first clinic visit. Results: The current analysis included 591 pregnancies from six cohorts, of which 73% were exposed to HCQ during pregnancy. Fetal loss: Overall, there was a 51% decrease in the risk of fetal loss among patients taking HCQ during pregnancy (OR: 0.49; 95% CI: 0.24 to 1.00). Among patients with a history of lupus nephritis, taking HCQ during pregnancy reduced the risk of fetal loss by 76% (OR: 0.24; 95% CI: 0.07 to 0.83; table 1). Preterm birth: There was no evidence that HCQ decreased the risk of preterm birth. Disease activity: Although not significant, among patients with a history of lupus nephritis, HCQ use during pregnancy may reduce the risk of having high disease activity during pregnancy (OR: 0.47; 95% CI: 0.21 to 1.09). Preeclampsia: Overall, there was no evidence that HCQ decreased the risk of. Among patients with APS, there may be a protective effect of HCQ, but the precision of the estimate was limited (OR: 0.55; 95% CI: 0.12 to 2.45). Conclusion: Our results suggest that among patients with lupus nephritis, HCQ use may decrease the risk of fetal loss and decrease high disease activity during pregnancy. The heterogeneity of data collection suggests the need for a unified approach to identify larger cohorts of lupus pregnancies.